Correction: Low Prevalence of Conjunctival Infection with Chlamydia trachomatis in a Treatment-Naïve Trachoma-Endemic Region of the Solomon Islands. - Robert M R Butcher; Oliver Sokana; Kelvin Jack; Colin K Macleod; Michael Marks; Eric Kalae; Leslie Sui; Charles Russell; Helena J Tutill; Rachel J Williams; Judith Breuer; Rebecca Willis; et al. (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004863.].